Recommendations on simple but transformative diversity, equity, and inclusion measures in Heliophysics over the next decade - Jones, McArthur; Burrell, Angeline G.; Gannon, Jennifer L.; Halford, Alexa J.; Jaynes, Allison N.; Maute, Astrid; Thiero, Kadidia (Frontiers in Astronomy and Space Sciences, 2022)
It is well established that, in order to perform at their peak ability, a person must feel accepted, safe, and valued at work. Therefore, it is imperative to bring Diversity, Equity, and Inclusion (DEI) efforts to the forefront of Heliophysics over the next decade and well beyond. This position paper outlines three specific recommendations to make the Heliophysics community more diverse, equitable, and inclusive by improving the accessibility and accountability. These recommendations are: performing consistent collection and analysis of demographic data across different agencies, reimagining undergraduate Heliophysics internships using the SOARS® model, and providing conference funding for DEI speakers whose expertise lies outside the field of Heliophysics. These targeted recommendations have a well-documented positive impact, are simple to implement, and follow other scientific communities’ recent recommendations for making the science, technology, engineering, and mathematics fields more diverse, equitable, and inclusive.